Audit Manajemen Teknologi Informasi Pada PT XYZ Menggunakan Framework COBIT 5 - Yunda Heningtyas; Akmal Junaidi; Yusikania Dwi Putri (Jurnal Komputasi, 2019)
PT XYZ is an agri-food company that has used the information technology for its company's operations. Information technology management at PT XYZ requires an audit to determine the level of information technology capability on PT XYZ and it provides a recommendations for business process improvements to achieve the business objectives of the company. Since this audit is intended to assess the managerial and technical aspect of information technology, audit of PT XYZ is conducted by applying COBIT 5 framework. Procedure of COBIT 5 consists of audit plans, audit preparation phase, the implementation phase of the audit, and audit reporting stage. This audit measures the capability level of information technology management at the sub-domain Manage Strategy (APO02) Manage Enterprise Architecture (APO03) Manage Relationships (APO08) Manage Suppliers (APO10) Manage Requirements Definition (BAI02) Identification Solutions Manage and Build (BAI03), and Manage Knowledge (BAI08). Based on evaluation using COBIT 5, PT XYZ is in the level 2.6 out of 5. Due to the rounding index value, the measurement results are at level 3 (Established Process) while the company's expectation level is at level 5. The level difference occurs because PT XYZ has not conducted a review, evaluation, and report of the settlement. Therefore, companies need to improve information technology management in achieving the company's business goals.